Rancang Bangun Sistem Kendali Berbasis PLC Dalam Mendukung Praktikum Dasar Sistem Kendali - Putri, Sherlyana Hardiyandeffi; Setiawan, Cahya Heru; Setiawan, Rudi (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2024)
A Programmable Logic Controller (PLC) is one of the control systems used in radar. Cadets at the Air Force Academy (AAU) are trained to become officers ready for deployment. Therefore, the author initiated the creation of a simple control system using a PLC, applied to traffic light management at a three-way intersection. It is hoped that this system will be used in basic control system practicals, thereby enhancing the knowledge and understanding of electronics students at the Air Force Academy, preparing them for their future assignments. The traffic light control system operates on a pre-determined schedule, with light changes to manage traffic. The traffic lights used in this study are based on a Mitsubishi FX3U 24MR PLC. This setup includes an input switch (selector switch), three traffic lights (red, yellow, and green), and a 24V DC 5A power supply adapter. The software design for the three-way traffic light system uses Mitsubishi FX3U PLC and is programmed using GX WORK 2 with a ladder diagram. Test results show that when the selector switch is on at input X001, all outputs from Y000 to Y010 indicate on or illuminated according to the time durations specified in timers T0 to T8. The research successfully designed and programmed the ladder logic to operate the traffic light timing conditions. The prototype of the three-way traffic light system based on the Mitsubishi FX3U PLC works effectively as a simple input-output control system. However, this research highlights the need for further development to enhance the effectiveness of the traffic light system in managing the speed and timing of each lane.